(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Nurses, as the largest segment of the health care workforce, are uniquely positioned to drive improvements in health care access, quality, and equity. This article explores four key areas where nurses can make a significant impact: increasing access for underserved populations, providing high-quality person-centered care, addressing social determinants of health, and advocating for policy changes. By leveraging nurses’ skills, patient relationships, and presence across care settings, health systems can accelerate progress toward achieving optimal health for all. Nurses are improving access through community-based care and telehealth, promoting quality by tailoring care to patient needs, addressing social determinants of health through innovative roles and partnerships, and advocating for policies to create healthier conditions. Realizing nurses’ full potential will require removing barriers to practice, investing in education and new care models, and dismantling structural racism. Nurses’ trusted voice and expertise position them to lead the movement toward health equity.